Production process of high-performance zinc-iron yellow prepared by separating and recycling waste acid of hot galvanizing
By using a composite complex crystal form regulator and urea in the hot-dip galvanizing waste acid preparation process, combined with an external circulation system and a Venturi jet injector, the reaction temperature and pH value are controlled to form dense microcrystalline particles. This solves the problems of low brightness and tinting strength and foam overflow in zinc iron yellow pigment, and achieves stable production of high-performance zinc iron yellow pigment.
Patent Information
- Application Number
- CN202611160131.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-08-03
AI Technical Summary
In the existing process for preparing zinc iron yellow pigment from waste acid from hot-dip galvanizing, the resulting colloidal precursor precipitate is difficult to dehydrate and wash away the chloride ions encapsulated inside, resulting in low brightness and coloring power of the calcined product. Furthermore, the introduction of polymeric additives can easily generate foam, causing the reaction liquid to overflow.
By combining a complex crystal form regulator with urea, and through a combination of an external circulation system and a Venturi jet injector, the reaction temperature gradient and pH value are controlled to form dense microcrystalline particles, ensuring thorough washing of chloride ions and lattice rearrangement, and avoiding foam aggregation.
This invention achieves zinc iron yellow pigment products with high tinting strength and high brightness, solves the problems of lattice distortion and foam overflow in traditional processes, and improves production stability and product quality.
Smart Images

Figure CN122667633B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid waste resource utilization technology, specifically a production process for separating and recovering hot-dip galvanizing waste acid to prepare high-performance zinc iron yellow. Background Technology
[0002] The hot-dip galvanizing process in steel production generates a large amount of waste acid solution rich in free hydrochloric acid, ferrous ions, and zinc ions. Resource recovery from this waste acid solution, including the extraction of iron and zinc elements to prepare zinc-iron composite pigments, is an important research direction in industrial solid waste treatment.
[0003] Currently, in industrial processes for treating such waste acid to prepare pigment precursors, the common practice is to directly add strong alkaline solutions such as sodium hydroxide or ammonia to the waste acid for neutralization and precipitation, combined with bottom microporous aeration to introduce air for oxidation. However, this conventional process has significant limitations in actual operation. Upon contact between the strong alkaline solution and the acidic waste acid, a pH gradient is generated in the fluid mixing zone. Excessively high local supersaturation causes metal ions to nucleate explosively within a short time, often resulting in highly amorphous or gel-like hydroxide precipitates. These loose and viscous colloidal materials generate significant fluid resistance in the subsequent solid-liquid separation stage, leading not only to long filter press dewatering cycles and high final moisture content in the filter cake, but also to trap chloride ions from the mother liquor within their complex capillary channels. Under conventional filter press washing conditions, the washing water easily short-circuits along the fissures, making it difficult to fully displace the chloride ions trapped inside the precipitate particles.
[0004] When a precursor filter cake containing a high concentration of residual chloride ions enters a rotary kiln for high-temperature dehydration and phase transformation, the chloride ions in the interstitial spaces induce lattice distortion. This causes the normally ordered rearrangement of the zinc-iron composite crystal structure to partially collapse, resulting in a dark brown pigment powder after calcination. Macroscopically, this powder exhibits low brightness and diminished tinting strength, failing to meet the commercial application standards for high-quality pigments. Simultaneously, to improve the crystallization state of the precipitated material, some existing processes attempt to introduce polymeric surfactants as crystal form regulators into the reaction system.
[0005] However, in practical engineering applications, the addition of polymeric additives alters the surface tension of the fluid. Combined with the traditional bottom-bubbling aeration oxidation method, the reaction system generates a large number of difficult-to-disrupt micro-foams during aeration. As the oxidation reaction proceeds, the foam rapidly accumulates in the reactor and occupies the effective volume, easily causing equipment overflow accidents and making it difficult to achieve stable continuous production. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides a production process for separating and recovering waste acid from hot-dip galvanizing to prepare high-performance zinc iron yellow. This process solves the problems in traditional hot-dip galvanizing waste acid processes for preparing zinc iron yellow pigment, such as the difficulty in dehydrating the generated colloidal precursor precipitate and washing away the internally encapsulated chloride ions, which leads to lattice distortion in the final calcined product, resulting in low brightness and tinting strength. It also addresses the problem that introducing polymeric additives in conjunction with bottom aeration oxidation easily generates a large amount of foam, causing overflow of the reaction liquid.
[0007] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a production process for separating and recovering waste acid from hot-dip galvanizing to prepare high-performance zinc iron yellow, comprising the following steps: The hot-dip galvanized waste acid is pumped into the main reactor, and the mother liquor of the composite complex crystal form regulator is added and stirred and mixed. Then, urea is added and stirred and dissolved to obtain a mixed reaction solution. Start the external circulation system connected to the main reactor, draw the mixed reaction liquid out of the main reactor, and spray it back into the main reactor for circulation after passing through a tubular heat exchanger and a Venturi jet in sequence; Open the air intake port of the Venturi jet injector to draw in air and oxidize the mixed reaction liquid in the circulation. When the pH value and residual ferrous ion concentration of the reaction system reach the preset conditions, stop the air intake and circulation operation to obtain a mixed slurry. The mixed slurry is fed into a filter press for filtration. The filter cake obtained by filtration is washed with deionized water. After the chloride ion concentration in the washing liquid reaches the preset condition, compressed air is introduced to dehydrate the washed filter cake to obtain zinc iron yellow precursor filter cake. The zinc-iron yellow precursor filter cake is fed into a calcination device for calcination, followed by cooling and pulverization to obtain the final zinc-iron yellow pigment powder.
[0008] By adopting the above technical solution, this process achieves an organic combination of spatial decoupling of the reaction zone and crystal form control system, thereby obtaining high-performance pigment products with high tinting strength and high brightness. The specific reaction mechanism and innovative process include the following steps: A composite complex crystal structure regulator is added to hot-dip galvanizing waste acid. The rigid phenylpropane backbone of the lignin in this regulator becomes entangled with the flexible long chains of polyethylene glycol. During the primary particle formation stage, this polymer complex adsorbs onto the crystal nucleus surface, establishing a steric hindrance layer that prevents the irregular divergent growth of crystal faces along low-density directions. This spatial constraint causes the microcrystals to shrink inward and aggregate densely, transforming the resulting precipitate from a loose, viscous colloidal state into well-dispersed, high-density microcrystalline particles.
[0009] Urea is used as the alkali supplier and is dissolved by mixing with waste acid at room temperature. The hydrolysis of urea in water is an endothermic reaction, producing ammonia and carbon dioxide. The ammonia dissolves in the liquid phase to generate hydroxide ions. During subsequent heating, the urea hydrolysis rate increases slowly. This in-situ slow alkali release mechanism prevents localized high alkalinity concentration gradients within the reaction system, ensuring a uniform low supersaturation state throughout the reaction space.
[0010] The circulation system spatially separates the circulation pipeline from the main reactor. A constant temperature is maintained within the main reactor to meet the thermodynamic requirements of continuous urea hydrolysis for alkali production and crystal lattice growth. A tubular heat exchanger cools the reaction liquid flowing through the front end of the Venturi jet. Since the solubility of oxygen in the aqueous phase increases with decreasing temperature, the low-temperature zone within the pipeline provides excellent conditions for air dissolution. As the high-speed fluid flows through the throat of the Venturi jet, a negative pressure is generated, drawing in external air. The intense shear stress generated by the fluid within the tube forces the incoming air to break up into micron-sized bubbles. In this environment of low temperature and high interphase contact area, ferrous ions react with dissolved oxygen and water to generate ferric ions and release hydrogen ions.
[0011] The acidic fluid generated by the oxidation reaction in the external circulation pipeline is continuously sprayed back into the main reactor, where it mixes and neutralizes with the alkaline fluid generated by the hydrolysis of urea in the main reactor. The high-flow circulation pump enables the two independent kinetic processes of acid production and alkali production, which occur in different spaces, to form a macroscopic dynamic equilibrium, limiting the pH fluctuation range of the entire core oxidation period to a small range. At the same time, the closed pipeline jet process replaces the traditional bottom micropore aeration. The jet fluid is sprayed into the main reactor from below the liquid surface at a tangential angle, and the high-speed kinetic energy destroys the surfactant liquid film formed on the liquid surface.
[0012] The aforementioned precursor particles have a dense internal structure without closed pores, ensuring that all entrained chloride ions are exposed on the particle surface. During solid-liquid separation and washing, deionized water can easily penetrate the filter cake pores to completely replace and clean the residual chloride ions. When the pure, dense precursor enters the rotary kiln for calcination, the isomorphic substitution of zinc and iron ions proceeds smoothly during the heating and dehydration process. Without interference from impurity ions, the crystal lattice achieves perfect rearrangement, ultimately generating a pure positive phase zinc-iron yellow with very few grain boundary defects. The product exhibits outstanding light selective reflectivity.
[0013] Preferably, the composite complex crystal form regulator mother liquor is prepared by mixing sodium lignosulfonate and polyethylene glycol 400 in water at a mass ratio of 1:0.1 to 0.3.
[0014] By adopting the above technical solution, it is ensured that polyethylene glycol molecules can be appropriately grafted and intercalated into the side chain gaps of lignin macromolecules, so that the macromolecules do not agglomerate and flocculate due to excessively long flexible chains, nor lose the ability to cover the steric hindrance of the crystal surface due to excessively low proportions, thus establishing the optimal template-constrained configuration.
[0015] Preferably, the preparation process of the composite complex crystal form regulator mother liquor includes: adding the sodium lignosulfonate to deionized water to prepare an aqueous solution with a mass fraction of 15.0% to 20.0%; adding the polyethylene glycol 400 dropwise into the aqueous solution at a stirring speed of 200 to 300 rpm; heating the mixed solution to 60 to 70°C, stirring at a constant temperature for 1.5 to 2.5 hours, and then cooling it to room temperature.
[0016] By adopting the above technical solution, under the action of heating and set mechanical shear force, the hydroxyl end of polyethylene glycol molecules can be fully hydrogen bonded and entangled with the polar groups of sodium lignosulfonate, ensuring that the polymer regulator maintains structural stability in the high salinity environment of subsequent waste acid.
[0017] Preferably, the hot-dip galvanizing waste acid specifically comprises: a concentration of ferrous ions of 80.0–120.0 g / L; a concentration of zinc ions of 20.0–50.0 g / L; a concentration of free hydrochloric acid of 0.5–2.0 mol / L; and an initial temperature controlled at 20–30°C when pumped into the main reactor; the amount of the composite complex crystal form regulator mother liquor added, based on the converted pure solid content, accounts for 1.0%–2.5% of the total mass of the hot-dip galvanizing waste acid.
[0018] By adopting the above technical solution, in the waste acid within this limited concentration range, an appropriate amount of polymer mother liquor can completely cover all the nucleation centers in the solution system, avoiding excessive addition that would lead to an increase in the chemical oxygen demand in the subsequent washing wastewater, and also avoiding insufficient addition that would cause some crystals to become distorted.
[0019] Preferably, after starting the external circulation system connected to the main reactor, the synchronous temperature control of the main reactor and the tubular heat exchanger specifically includes: heating the main reactor at a heating rate of 0.8 to 1.5 °C / min to keep the temperature of the material inside the reactor constant at 85 to 95 °C; and using the tubular heat exchanger to cool the material in the pipeline to keep the temperature of the mixed reaction liquid flowing through the front section of the Venturi jet at 55 to 65 °C.
[0020] By adopting the above technical solution, the temperature gradient of the reaction zone was clarified. The main reactor temperature of 85-95℃ provides the necessary thermal energy to drive the stable hydrolysis of urea and the slow growth and rearrangement of crystals. The local cooling temperature of 55-65℃ breaks the thermodynamic limitation of high temperature on oxygen solubility, so that the system has the dual advantages of rapid mass transfer and stable nucleation.
[0021] Preferably, the step of opening the air intake port of the Venturi jet injector to draw in air specifically includes: drawing in air using fluid negative pressure, controlling the air intake volume to be 0.3 to 0.8 Nm3 / (h·m3); the pH value and residual ferrous ion concentration of the reaction system meet the preset conditions, including an online pH meter reading in the range of 4.8 to 5.2, and a residual ferrous ion concentration of less than 0.1 g / L.
[0022] By adopting the above technical solution, the oxygen inlet intensity was standardized, and the system was kept in a suitable redox potential range. The online pH setting range and the detection limit of ferrous ions were used together as the endpoint judgment criteria to ensure that all free ferrous ions in the system were converted and precipitated.
[0023] Preferably, the step of feeding the mixed slurry into a filter press for filtration and washing the filter cake obtained by filtration with deionized water specifically includes: pumping the mixed slurry into a plate and frame filter press, setting the pressure of the feed pump to 0.4-0.6 MPa; after no continuous filtrate flows out of the outlet, washing with deionized water, controlling the pressure of the washing water to 0.5-0.7 MPa, and controlling the amount of washing water per unit mass of dry filter cake to 1.5-2.5 L / kg.
[0024] By adopting the above technical solution, the dense and non-water-retaining properties of the precursor particles can be utilized to achieve rapid liquid-solid separation of the mixed slurry under conventional feeding pressure, and deep dechlorination can be achieved by relying on washing water with extremely low specific consumption.
[0025] Preferably, after the chloride ion concentration in the washing solution reaches a preset condition, compressed air is introduced to dehydrate the washed filter cake to obtain the zinc-iron yellow precursor filter cake. Specifically, this includes: stopping the washing with deionized water when the chloride ion concentration in the washing solution is below 100 mg / L; introducing compressed air at a pressure of 0.6 MPa to purge and dehydrate the filter cake for 15-25 minutes; and then unloading the filter cake to obtain the zinc-iron yellow precursor filter cake.
[0026] By adopting the above technical solution, the capillary water between the filter cake particles is forcibly blown out by an airflow with a certain pressure, which further reduces the physical moisture content of the precursor filter cake when it enters the rotary kiln, thereby saving energy consumption in the subsequent evaporation and dehydration stage.
[0027] Preferably, the zinc-iron yellow precursor filter cake is fed into a roasting device for roasting treatment, followed by cooling and pulverization. Specifically, this includes: conveying the zinc-iron yellow precursor filter cake to a rotary roasting kiln, setting the heating rate to 3-5℃ / min, heating to 450-550℃, and roasting and oxidizing dehydration at a constant temperature for 2.0-4.0 hours; after roasting, the material is naturally cooled to below 80℃ in the furnace and then mechanically pulverized.
[0028] By adopting the above technical solution, under the set heating program and constant calcination temperature, the water of crystallization inside the precursor is stably removed, and the metal ions obtain sufficient migration activation energy to complete the isomorphic substitution and recombination of the solid phase lattice structure, thereby achieving the final shaping of the macroscopic pigment coloring power properties.
[0029] Preferably, the step of adding urea and stirring to dissolve includes calculating the amount of urea to be added based on 1.05 to 1.15 times the theoretically required alkalinity equivalent in the system, and adding the urea in solid particle form into the main reactor at once for stirring and dissolving.
[0030] By adopting the above technical solution, the solid direct addition method avoids the increase in the volume of the waste acid system caused by dissolution and dilution. The set excess coefficient can compensate for the small amount of ammonia gas lost during hydrolysis due to the exhaust system, ensuring sufficient alkalinity supply throughout the cycle.
[0031] This invention provides a production process for separating and recovering waste acid from hot-dip galvanizing to prepare high-performance zinc iron yellow. It has the following beneficial effects: 1. This invention utilizes a composite complex crystal form regulator composed of sodium lignosulfonate and polyethylene glycol to form a steric hindrance layer on the crystal nucleus surface through the entanglement structure of the two substances, restricting the disordered growth of crystal faces along low-density directions. This transforms the generated precursor precipitate from a conventional loose colloidal morphology into high-density microcrystalline particles. The dense particle structure reduces the encapsulation of the solution by internal pores, lowers the fluid resistance during solid-liquid separation, thereby shortening the pressure filtration and dewatering time and reducing the amount of washing water required for subsequent removal of residual chloride ions.
[0032] 2. This invention achieves temperature decoupling of the reaction zone by setting up an external circulation system and establishing a temperature gradient between the main reactor and the tubular heat exchanger. The high-temperature environment maintained in the main reactor provides the thermal energy required for stable urea hydrolysis and slow crystal growth; while the low-temperature environment maintained at the front end of the external circulation pipeline improves the fluid's ability to dissolve oxygen in the air. This zoned temperature control mechanism overcomes the problem of decreased oxygen mass transfer efficiency caused by high temperatures in traditional single-temperature zone operation, improving the oxidation conversion efficiency of iron ions while ensuring lattice development.
[0033] 3. This invention uses room-temperature dissolved urea as a slow-acting alkali supply agent, combined with a Venturi jet structure for negative pressure oxygenation. The slow hydrolysis of urea with increasing temperature avoids localized supersaturation caused by directly adding conventional strong alkali, ensuring crystal nucleation in a uniform environment. Simultaneously, a high-speed jet is tangentially injected into the main reactor, utilizing fluid kinetic energy to disrupt the surfactant film formed on the liquid surface, suppressing bubble aggregation and overflow during aeration. These operations ensure the orderliness of the crystallization process, reduce lattice distortion, and enable the final calcined zinc iron yellow pigment powder to possess both brightness and tinting strength. Attached Figure Description
[0034] Figure 1 This is a comparison diagram of the reaction fluid dynamics and kinetics monitoring of the present invention; Figure 2 This is a comparison chart of the stability of the reaction process due to changes in acidity and alkalinity in the present invention. Figure 3 This is a graph showing the comprehensive test results of the solid-liquid separation efficiency and dechlorination washing status of the mixed slurry in various process schemes of the present invention; Figure 4 This is a comparison chart of the macroscopic pigment properties of the final zinc iron yellow products from various process schemes of the present invention. Detailed Implementation
[0035] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0036] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.
[0037] Urea, CAS number 57-13-6, is a commercially available industrial-grade product.
[0038] Sodium lignosulfonate, CAS number 8061-51-6.
[0039] Polyethylene glycol 400, CAS number 25322-68-3.
[0040] Sodium hydroxide, CAS number 1310-73-2, is a commercially available analytical grade reagent.
[0041] Preparation Examples 1-3: Preparation Example 1: This preparation example provides a method for preparing a composite complex crystal form regulator, including the following steps: Take deionized water and add sodium lignosulfonate at room temperature to prepare a sodium lignosulfonate aqueous solution with a mass fraction of 15.0%.
[0042] Turn on the mechanical stirrer and set the speed to 200 rpm. Add polyethylene glycol 400 slowly dropwise into the above aqueous solution at a mass ratio of sodium lignosulfonate to polyethylene glycol 400 of 1:0.1.
[0043] The mixed solution was heated to 60°C, stirred at a constant temperature for 1.5 hours, and then cooled to room temperature to obtain a composite complex crystal form regulator for later use.
[0044] Preparation Example 2: This preparation example provides a method for preparing a composite complex crystal form regulator, including the following steps: Take deionized water and add sodium lignosulfonate at room temperature to prepare a sodium lignosulfonate aqueous solution with a mass fraction of 17.5%.
[0045] Turn on the mechanical stirrer and set the speed to 250 rpm. Add polyethylene glycol 400 slowly dropwise into the above aqueous solution at a mass ratio of sodium lignosulfonate to polyethylene glycol 400 of 1:0.2.
[0046] The mixed solution was heated to 65°C and kept at that temperature for 2.0 hours with stirring. Then it was cooled to room temperature to obtain a composite complex crystal form regulator for later use.
[0047] Preparation Example 3: This preparation example provides a method for preparing a composite complex crystal form regulator, including the following steps: Take deionized water and add sodium lignosulfonate at room temperature to prepare a sodium lignosulfonate aqueous solution with a mass fraction of 20.0%.
[0048] Turn on the mechanical stirrer and set the speed to 300 rpm. Add polyethylene glycol 400 slowly dropwise into the above aqueous solution at a mass ratio of sodium lignosulfonate to polyethylene glycol 400 of 1:0.3.
[0049] The mixed solution was heated to 70°C, stirred and kept at that temperature for 2.5 hours, and then cooled to room temperature to obtain a composite complex crystal form regulator for later use.
[0050] Examples 1-4: Example 1: This example provides a production process for separating and recovering waste acid from hot-dip galvanizing to prepare high-performance zinc iron yellow, including the following steps: The hot-dip galvanizing waste acid (ferrous ion concentration of 120.0 g / L, zinc ion concentration of 20.0 g / L, and free hydrochloric acid concentration of 0.5 mol / L) was pumped into a jacketed, temperature-controlled main reactor, maintaining an initial temperature of 20°C. The main reactor was stirred at 150 rpm. Based on the calculated pure solid content, 1.0% of the composite complex crystal form regulator mother liquor obtained in Preparation Example 1 was added, and stirring continued for 30 minutes. The urea dosage was calculated based on 1.05 times the theoretically required alkalinity equivalent within the system. Solid granular urea was added to the main reactor in one batch and stirred until dissolved.
[0051] Start the external circulation system of the main reactor. The material is drawn out from the bottom of the main reactor and enters the tubular heat exchanger via a centrifugal pump. It then flows through the Venturi jet injector and finally is sprayed back into the main reactor at a tangential angle from 30 cm below the liquid surface through the discharge pipe of the Venturi jet injector. Set the flow rate of the external circulation pump to control the circulation ratio at 2.0 h. -1 Start the main reactor jacket heating, and heat the material in the main reactor at a heating rate of 0.8℃ / min. Use a temperature controller to keep the main reactor temperature constant at 85℃. Simultaneously turn on the shell-side cooling water medium of the tubular heat exchanger to control the temperature of the material flowing through the external circulation pipeline in front of the Venturi jet and keep it at 55℃.
[0052] After the circulating fluid temperature stabilizes and a gradient is established, open the air intake valve of the Venturi ejector to draw in atmospheric pressure air using the fluid's negative pressure, controlling the intake flow rate to 0.3 Nm. 3 / (h·m) 3 When the online pH meter reading stabilizes at 4.8 and the residual ferrous ion concentration is found to be below 0.1 g / L, close the air intake and stop heating and external circulation.
[0053] The obtained slurry was directly pumped into a plate and frame filter press for filtration, with the feed pump pressure set at 0.4 MPa. After no continuous filtrate flowed from the outlet, the filter cake was washed with deionized water at a pressure controlled at 0.5 MPa, with a washing water volume of 1.5 L / kg of dry filter cake. Washing was stopped when the chloride ion concentration in the washing liquid fell below 100 mg / L. Compressed air at 0.6 MPa was then introduced to purge and dehydrate the filter cake for 15 minutes. The resulting zinc-iron yellow precursor filter cake was then discharged. The initial filtrate and the initial washing liquid were combined and sent to the evaporation and crystallization system.
[0054] The discharged precursor filter cake is transported to a rotary kiln, and the roasting heating rate is set to 3℃ / min. The material is heated to 450℃ and roasted at a constant temperature for 2.0 hours for oxidation and dehydration. After roasting, the material is naturally cooled to below 80℃ in the furnace and then mechanically crushed to obtain the final zinc iron yellow pigment powder.
[0055] Example 2: This example provides a production process for separating and recovering waste acid from hot-dip galvanizing to prepare high-performance zinc iron yellow, including the following steps: The hot-dip galvanizing waste acid (ferrous ion concentration of 100.0 g / L, zinc ion concentration of 35.0 g / L, and free hydrochloric acid concentration of 1.2 mol / L) was pumped into a jacketed, temperature-controlled main reactor, and the initial temperature inside the main reactor was controlled at 25°C. The main reactor was stirred at 200 rpm. Based on the calculated pure solid content, 1.75% of the composite complex crystal form regulator mother liquor obtained in Preparation Example 2 was added, and stirring was continued for 40 minutes. The amount of urea added was calculated based on 1.10 times the theoretically required alkalinity equivalent in the system, and solid granular urea was added to the main reactor in one go and stirred to dissolve.
[0056] Start the external circulation system of the main reactor. The material is drawn out from the bottom of the main reactor and enters the tubular heat exchanger via a centrifugal pump. It then flows through the Venturi jet injector and finally is sprayed back into the main reactor at a tangential angle from 40 cm below the liquid surface through the discharge pipe of the Venturi jet injector. Set the flow rate of the external circulation pump to control the circulation ratio at 3.0 h. -1 Start the main reactor jacket heating, and heat the material in the main reactor at a heating rate of 1.0℃ / min. Use a temperature controller to keep the main reactor temperature constant at 90℃. Simultaneously turn on the shell-side cooling water medium of the tubular heat exchanger to control the temperature of the material flowing through the external circulation pipeline in front of the Venturi jet and keep it at 60℃.
[0057] After the circulating fluid temperature stabilizes and a gradient is established, open the air intake valve of the Venturi ejector to draw in atmospheric pressure air using the fluid's negative pressure, controlling the intake flow rate to 0.5 Nm. 3 / (h·m) 3 When the online pH meter reading stabilizes at 5.0 and the residual ferrous ion concentration is found to be below 0.1 g / L, close the air intake and stop heating and external circulation.
[0058] The obtained slurry was directly pumped into a plate and frame filter press for filtration, with the feed pump pressure set at 0.5 MPa. After no continuous filtrate flowed from the outlet, the filter cake was washed with deionized water at a pressure controlled at 0.6 MPa, with a washing water volume of 2.0 L / kg of dry filter cake. Washing was stopped when the chloride ion concentration in the washing solution fell below 100 mg / L. Compressed air at 0.6 MPa was then introduced to purge and dehydrate the filter cake for 20 minutes. The resulting zinc-iron yellow precursor filter cake was then discharged. The initial filtrate and the initial washing solution were combined and sent to the evaporation and crystallization system.
[0059] The discharged precursor filter cake is conveyed to a rotary kiln, and the roasting heating rate is set to 4℃ / min. The material is heated to 500℃ and roasted at a constant temperature for 3.0 hours for oxidation and dehydration. After roasting, the material is naturally cooled to below 80℃ in the furnace, and then mechanically crushed to obtain the final zinc iron yellow pigment powder.
[0060] Example 3: This example provides a production process for separating and recovering waste acid from hot-dip galvanizing to prepare high-performance zinc iron yellow, including the following steps: The hot-dip galvanizing waste acid (ferrous ion concentration of 80.0 g / L, zinc ion concentration of 50.0 g / L, and free hydrochloric acid concentration of 2.0 mol / L) was pumped into a jacketed, temperature-controlled main reactor, and the initial temperature inside the main reactor was controlled at 30°C. The main reactor was stirred at 250 rpm. Based on the calculated pure solid content, 2.5% of the composite complex crystal form regulator mother liquor obtained in Preparation Example 3 was added, and stirring was continued for 45 minutes. The amount of urea added was calculated based on 1.15 times the theoretically required alkalinity equivalent in the system, and solid granular urea was added to the main reactor in one go and stirred to dissolve.
[0061] Start the external circulation system of the main reactor. The material is drawn out from the bottom of the main reactor and enters the tubular heat exchanger via a centrifugal pump. It then flows through the Venturi jet injector and finally is sprayed back into the main reactor at a tangential angle from 50 cm below the liquid surface through the discharge pipe of the Venturi jet injector. Set the flow rate of the external circulation pump to control the circulation ratio at 4.0 h. -1 Start the main reactor jacket heating, and heat the material in the main reactor at a heating rate of 1.5℃ / min. Use a temperature controller to keep the main reactor temperature constant at 95℃. Simultaneously turn on the shell-side cooling water medium of the tubular heat exchanger to control the temperature of the material flowing through the external circulation pipeline in front of the Venturi jet and keep it at 65℃.
[0062] After the circulating fluid temperature stabilizes and a gradient is established, open the air intake valve of the Venturi ejector to draw in atmospheric pressure air using the fluid's negative pressure, controlling the intake flow rate to 0.8 Nm. 3 / (h·m) 3 When the online pH meter reading stabilizes at 5.2 and the residual ferrous ion concentration is found to be below 0.1 g / L, close the air intake and stop heating and external circulation.
[0063] The obtained slurry was directly pumped into a plate and frame filter press for filtration, with the feed pump pressure set at 0.6 MPa. After no continuous filtrate flowed from the outlet, the filter cake was washed with deionized water at a pressure controlled at 0.7 MPa, with a washing water volume of 2.5 L / kg of dry filter cake. Washing was stopped when the chloride ion concentration in the washing solution fell below 100 mg / L. Compressed air at 0.6 MPa was then introduced to purge and dehydrate the filter cake for 25 minutes. The resulting zinc-iron yellow precursor filter cake was then discharged. The initial filtrate and the initial washing solution were combined and sent to the evaporation and crystallization system.
[0064] The discharged precursor filter cake is conveyed to a rotary kiln, and the roasting heating rate is set to 5℃ / min. The material is heated to 550℃ and roasted at a constant temperature for 4.0 hours for oxidation and dehydration. After roasting, the material is naturally cooled to below 80℃ in the furnace, and then mechanically crushed to obtain the final zinc iron yellow pigment powder.
[0065] Example 4: This example provides a production process for separating and recovering waste acid from hot-dip galvanizing to prepare high-performance zinc iron yellow, including the following steps: The hot-dip galvanizing waste acid (ferrous ion concentration of 80.0 g / L, zinc ion concentration of 50.0 g / L, and free hydrochloric acid concentration of 2.0 mol / L) was pumped into a jacketed, temperature-controlled main reactor, maintaining an initial temperature of 25°C. The main reactor was stirred at 200 rpm. Based on the calculated pure solid content, 1.75% of the composite complex crystal form regulator mother liquor obtained in Preparation Example 2 was added, and stirring continued for 40 minutes. The urea dosage was calculated as 1.10 times the theoretically required alkalinity equivalent in the system, and solid granular urea was added to the main reactor in one go, stirring until dissolved.
[0066] Start the external circulation system of the main reactor. The material is drawn out from the bottom of the main reactor and enters the tubular heat exchanger via a centrifugal pump. It then flows through the Venturi jet injector and finally is sprayed back into the main reactor at a tangential angle from 40 cm below the liquid surface through the discharge pipe of the Venturi jet injector. Set the flow rate of the external circulation pump to control the circulation ratio at 3.0 h. -1 Start the main reactor jacket heating, raising the temperature of the material inside the main reactor at a rate of 1.0℃ / min, and use a temperature controller to maintain the main reactor temperature at 90℃. Simultaneously turn on the shell-side cooling water medium of the tubular heat exchanger to control the temperature of the material flowing through the external circulation pipeline before the Venturi jet and maintain it at 60℃.
[0067] After the circulating fluid temperature stabilizes and a gradient is established, open the air intake valve of the Venturi ejector to draw in atmospheric pressure air using the fluid's negative pressure, controlling the intake flow rate to 0.5 Nm. 3 / (h·m) 3When the online pH meter reading stabilizes at 5.0 and the residual ferrous ion concentration is found to be below 0.1 g / L, close the air intake and stop heating and external circulation.
[0068] The obtained slurry was directly pumped into a plate and frame filter press for filtration, with the feed pump pressure set at 0.5 MPa. After no continuous filtrate flowed from the outlet, the filter cake was washed with deionized water at a pressure controlled at 0.6 MPa, with a washing water volume of 2.0 L / kg of dry filter cake. Washing was stopped when the chloride ion concentration in the washing solution fell below 100 mg / L, and the filter cake was purged and dehydrated with compressed air at 0.6 MPa for 20 minutes. The resulting zinc-iron yellow precursor filter cake was then discharged. The initial filtrate and the initial washing solution were combined and sent to the evaporation and crystallization system.
[0069] The discharged precursor filter cake is conveyed to a rotary kiln, and the roasting heating rate is set to 4℃ / min. The material is heated to 500℃ and roasted at a constant temperature for 3.0 hours for oxidation and dehydration. After roasting, the material is naturally cooled to below 80℃ in the furnace, and then mechanically crushed to obtain the final zinc iron yellow pigment powder.
[0070] Comparative Examples 1-5: Comparative Example 1: Compared with Example 2, the difference is that no composite complex crystal form regulator and urea are added, the external circulation system and Venturi jet of the main reactor are removed, a 30% sodium hydroxide aqueous solution is slowly added directly to the main reactor to adjust the pH value, and air is introduced through the conventional microporous gas distribution pipe at the bottom of the main reactor for oxidation. All other aspects are the same.
[0071] Comparative Example 2: Compared with Example 2, the difference is that the shell-side cooling water medium of the tubular heat exchanger is turned off, so that the temperature of the material flowing through the external circulation pipeline and the Venturi jet is the same as that of the main reactor at 90°C, that is, no decoupled temperature gradient is established between the inside and outside. Everything else is the same.
[0072] Comparative Example 3: Compared with Example 2, the difference is that the Venturi jet at the end of the external circulation pipeline is removed, the external circulation fluid cooled to 60°C is directly discharged back to the main reactor, and the air required for oxidation is instead blown directly into the main reactor through the microporous gas distribution pipe at the bottom of the main reactor. All other aspects are the same.
[0073] Comparative Example 4: Compared with Example 2, the difference is that no complex complex crystal form regulator is added in the pre-complexation step, and all other steps are the same.
[0074] Comparative Example 5: Compared with Example 2, the difference is that the mother liquor of the complex complex crystal form regulator added in the pre-complexing step is replaced by an equal amount of a single sodium lignosulfonate aqueous solution with a mass fraction of 17.5%, and all other aspects are the same.
[0075] Test Examples 1-4: Test Example 1: Test Objective: To verify whether the temperature difference decoupled external circulation jet process can improve the oxygen mass transfer rate and overall oxidation reaction kinetics of the system while suppressing the severe foaming tendency of the surfactant system.
[0076] Experimental steps: Based on the complete production process conditions set in Examples 1 to 4 and Comparative Examples 1 to 5, the corresponding formulas and parameters of each group were applied to the same specification main reactor with sight glass and external circulation system for parallel testing. Once the reaction begins, the pipeline is opened to introduce air for oxidation. During this stage, the scale recording system of the sight glass on the side wall of the main reactor is kept on throughout the process to periodically observe and record the maximum vertical height of the foam accumulation layer above the liquid surface. As the reaction progresses, at regular intervals after the air is introduced, a small amount of the reaction solution is extracted through a sampling port with a valve, and the filtrate is immediately filtered through a microporous membrane to retain the filtrate. The concentration of ferrous ions in the extracted filtrate was quantitatively analyzed by titration with potassium dichromate standard solution, and the concentration decay was continuously monitored. When two consecutive samples show that the concentration of ferrous ions in the filtrate is below 0.1 g / L, the oxidation reaction is considered to have reached its endpoint, and the total time elapsed from the start of air introduction to that point is recorded.
[0077] The experimental results are shown in Table 1: Table 1: Monitoring Data of Fluid Dynamics and Oxidation Kinetics in the Reaction Process
[0078] in conclusion: Figure 1 This is a comparison chart of the reaction fluid dynamics and kinetics monitoring of various embodiments and comparative examples of the present invention. Figure 1 The vertical axis on the left and the solid square broken line represent the time required for the oxidation reaction to fully reach the target. The numerical points corresponding to this line reflect the differences in the oxidation reaction rate of Examples 1 to 4 and Comparative Examples 1 to 5. Figure 1 The vertical axis on the right and the dashed circle line represent the maximum foam layer height. The markers on this line visually represent the foaming tendency of the corresponding test object during the reaction process.
[0079] According to the data in Table 1, the temperature difference decoupled external circulation jet process designed in this invention exhibits a key technical synergy effect in terms of hydrodynamic stability and mass transfer dynamics. Conventional air bubbling processes often face insurmountable engineering obstacles after the introduction of polymeric surfactants. As revealed by the data in Comparative Example 3, when using microporous air distribution pipes to directly aerate the main reactor containing sodium lignosulfonate, amphiphilic molecules rapidly align at the gas-liquid interface and form a highly viscoelastic liquid film, causing the foam height to rise uncontrollably to 156.4 cm and even triggering severe overflow.
[0080] To address this chemical limitation, Examples 1 to 4 employ a closed-pipe jet strategy to create a fluid environment that disrupts the bubble-stabilizing mechanism. The intense shear stress generated by the high-speed fluid in the Venturi tube section forces the intake air to tear into micron-sized bubbles, which then complete gas-liquid mixing within the closed pipe. Finally, the bubbles return to the reactor in a tangential jet below the liquid surface. This kinetic energy conversion not only avoids the rise of the surface liquid film but also firmly suppresses the bubble height within a safe range of 3.2 to 5.8 cm.
[0081] Further examination of the test results from the reaction kinetics perspective reveals that the spatial temperature gradient decoupling mechanism is the core driving force for maintaining efficient oxidation throughout the entire cycle. In practical engineering, high-temperature conditions can lead to a thermodynamic drop in gas solubility. In Comparative Example 2, under a uniform temperature of 90 degrees Celsius across the entire reactor, the dissolution and diffusion of oxygen in the aqueous phase almost ceased, causing the oxidation reaction time to be drastically extended to 863 minutes. This demonstrates that relying solely on high temperatures to accelerate the intrinsic rate of the chemical reaction itself is actually hampered by the extremely deteriorated interfacial mass transfer efficiency.
[0082] The process design of this invention cleverly circumvents this contradiction. With the intervention of the heat exchanger, the external circulation pipeline is forcibly cooled to a relatively low temperature range of 60 degrees Celsius. In this region, the gas obtains excellent solubility thermodynamic conditions. Combined with the large interphase contact area provided by the jet microbubbles, ferrous ions are rapidly oxidized to produce acid. The highly active fluid rich in ferric iron is then pumped back to the main reactor at 90 degrees Celsius, where it undergoes isomorphous displacement precipitation with the alkalinity generated by the slow hydrolysis of urea. The overall time for this embodiment is reduced to 268 to 392 minutes. This engineering approach, which spatially separates the contradictory conditions of gas-liquid mass transfer and crystal growth and establishes a dynamic equilibrium through a circulation pump, fundamentally revitalizes the process path for the high-value utilization of waste acid from hot-dip galvanizing.
[0083] Test Example 2: Test Objective: To verify whether macroscopic neutralization can be achieved between the slow high-temperature hydrolysis of urea to produce alkali and the oxidation of acid in the jet zone under spatially decoupled conditions, thereby eliminating local concentration gradients and constructing a stable homogeneous precipitation environment.
[0084] Experimental steps: Based on the formulations and process parameters of Examples 1 to 4 and Comparative Examples 1 to 5, prepare corresponding volumes of hot-dip galvanizing waste acid and other raw materials, and configure the same reaction and monitoring hardware equipment. An industrial-grade, high-temperature resistant online pH meter probe, calibrated with a standard buffer solution, is installed below the liquid level in the main reactor and connected to the data acquisition terminal. Record the pH value of each group of materials at room temperature in the initial state, and then start the heating cycle or the dripping system to formally enter the reaction cycle; The data acquisition terminal continuously records and stores the pH value of the system throughout the entire oxidation reaction cycle at a fixed sampling frequency of 5 minutes. All pH data records were extracted from the core reaction period from the introduction of air until the concentration of ferrous ions reached the target. The highest and lowest values were screened out, and the process with poor environmental stability was calculated.
[0085] The experimental results are shown in Table 2: Table 2: Test Data of Extreme Values and Fluctuation Range of Acidity and Alkalinity During the Reaction Process
[0086] in conclusion: Figure 2 This is a comparison chart of the pH evolution stability of the reaction processes in various embodiments and comparative examples of the present invention. The left vertical axis and vertical line segments in the figure show the distribution range of the highest pH value (white inverted triangle mark) and the lowest pH value (black upright triangle mark) of each test object during the core reaction period, reflecting the extreme acid and alkaline environment shocks encountered by the reaction system; the right vertical axis and dashed broken line represent the calculated fluctuation range, quantitatively revealing the severity of the overall pH drift.
[0087] According to the data in Table 2, the stability of the pH evolution within the system directly confirms the successful construction of a biochemical-grade homogeneous precipitation environment. In traditional iron-based pigment synthesis research, colloidal nucleation caused by localized over-alkali is often the core problem leading to a high specific resistance of the final powder and difficulty in washing. Comparative Example 1 used a conventional sodium hydroxide solution dropwise addition method. The lag in fluid mixing inevitably resulted in an extremely high pH region near the alkali inlet, with a fluctuation range as high as 2.16 during the core reaction period. This drastic environmental change forces iron ions to instantly form flocculent amorphous hydroxides, making it impossible to maintain the low supersaturation conditions for slow lattice growth.
[0088] In Examples 1 to 4, the hydrolysis of urea was activated by the high-temperature environment of the main reactor, while the jet oxidation of ferrous ions to produce acid was confined to the lower-temperature external circulation cooling zone. This deliberately spatially separated acid and alkali production process achieved a dynamic neutralization on a macroscopic scale through a high-flow-rate circulation pump, with the range of the entire core stage strictly compressed within a tiny range of 0.25 to 0.46. The smooth evolution curve not only completely suppressed the explosive aggregation of primary precipitate particles but also provided sufficient relaxation time for zinc-iron isomorphous substitution and lattice rearrangement.
[0089] Exploring the root cause of the difference between homogeneous and differential temperature systems, comparative data from Example 2 reveals that when the tubular heat exchanger is removed, resulting in a total temperature of 90 degrees Celsius, the rate of urea alkali release exceeds the rate of acid production due to oxidation under low oxygen solubility. This imbalance between alkali supply and acid production rates leads to rapid alkaliization in the early stages of the system, deviating from the theoretical equilibrium point and amplifying the range to 1.07. This clearly demonstrates that without applying differentiated temperature constraints to the two kinetically independent processes of alkali supply and acid production, it is impossible to maintain an ideal slightly acidic homogeneous interface throughout the entire cycle, inevitably leading to variations in the material's phase structure.
[0090] Test Example 3: Test Objective: To verify the actual effect of the process of the present invention in reducing the filtration resistance of precipitated materials, improving dewatering performance, and reducing the amount of dechlorination washing water from an engineering application perspective.
[0091] Experimental steps: After the oxidation precipitation reaction in each embodiment and comparative example reached the predetermined endpoint, 50.0 liters of untreated original mixed slurry were extracted from the corresponding main reactor, placed in a transfer tank and stirred at a low speed to prevent particle sedimentation. Each group of slurry was pumped into a laboratory small plate and frame filter press of the same specifications. The feed pump was started and the feed pressure was kept constant at 0.5MPa. The total filtration time from the opening of the feed valve to the point when no more continuous filtrate flowed out of the outlet pipe was recorded. The filter cake inside the filter press chamber is washed with deionized water, and the inlet pressure of the washing water is maintained at 0.6 MPa. The washing effluent is sampled every 5 minutes and the concentration of free chloride ions is detected. When the concentration of free chloride ions in the washing liquid drops to below 100 mg / L, the washing water pumping should be stopped immediately, the total volume of deionized water consumed in the process should be recorded, and the washing water consumption per unit mass of dry filter cake should be calculated by combining the mass of dry sludge in the later stage. Compressed air at 0.6 MPa was introduced into the filter press to perform a constant-time 20-minute penetration purging dewatering of the washed filter cake. Then, the plate and frame were opened for unloading. Approximately 500 grams of the unloaded filter cake were randomly sampled from multiple points in each group and placed in a 105°C forced-air drying oven to be dried to constant weight. The final moisture content of the filter cake was calculated by the weight loss method.
[0092] The experimental results are shown in Table 3: Table 3: Test Data on Solid-Liquid Separation and Dehydration Washing Efficiency of Mixed Slurry
[0093] in conclusion: Figure 3 This is a comprehensive test result diagram of the solid-liquid separation efficiency and dechlorination washing status of the mixed slurry of various process schemes of the present invention. Sub-figure (a) shows the distribution of filter press time under the same operating pressure through solid square needle diagrams, and presents the final moisture content of the filter cake at the time of unloading with hollow triangular broken lines. Sub-figure (b) uses gray filled areas and solid dotted lines to reflect the volume of deionized water required per unit mass of dry matter for each test group when washing the filter cake to the same low chloride ion residual standard, covering the complete comparative sequence of Examples 1 to 4 and Comparative Examples 1 to 5.
[0094] According to the data in Table 3, the density and surface charge characteristics of the solid precipitate generated during the resource recycling process of hot-dip galvanizing waste acid have a decisive impact on subsequent separation and purification. In the past, engineering sites frequently encountered the problem of filter press pump stalling or incomplete washing water penetration due to the hydrogel-like state of the precipitate. This industrial pain point was directly reproduced in Comparative Example 1. Directly adding alkaline solution disrupted the homogeneous state of the system, resulting in highly amorphous iron-oxygen hydrates. The sponge-like microstructure tightly sealed a large amount of free water and sodium chloride mother liquor within the pores, causing the feed filtration time to soar to 153.7 minutes, and the water content after forced dehydration was still as high as 62.3%. This loose, gel-like filter cake created a resistance channel short-circuit effect on the washing water flow, with most of the water flowing away along the cracks and unable to displace impurities within the micropores. As a result, 7.85 liters of deionized water were required per kilogram of dry sludge to barely complete dechlorination.
[0095] The performance of the example groups demonstrates the structural remodeling process following temperature decoupling and the intervention of the composite crystal form regulator; when the homogeneous system provides a stable, slightly acidic substrate for lattice growth, sodium lignin sulfonate and polyethylene glycol 400 play a specific template role in the liquid phase. Reflecting on the data from Comparative Examples 4 and 5, it is evident that while relying solely on temperature and flow field control can reduce the filtration time to 76.8 min, or adding lignin alone can control the moisture content to 42.1%, neither can achieve the ultimate particle density.
[0096] In Example 2, the combination of the rigid phenylpropane skeleton of lignin and the flexible polyethylene glycol segments forms a steric hindrance layer on the surface of the primary particles, inhibiting the divergent growth of crystal faces along irregular low-density directions and forcing the particles to aggregate densely. The reaction product transforms from a sticky colloid into highly dispersed, high-density microcrystalline particles, allowing the filtrate to rapidly penetrate and empty within 38.6 minutes. More importantly, the removal of excess mesopores on the surface of the dense particles leaves chloride ions nowhere to hide, requiring only a trace amount of washing water (1.42 liters / kg) to thoroughly rinse them away. The improvement in the macroscopic properties of the particles is essentially a natural result of the comprehensive domestication of precipitation and crystallization kinetics.
[0097] Test Example 4: Test Objective: By testing the color development parameters and coloring efficiency of the final calcined products prepared by different process schemes in the optical system, this test aims to verify the decisive role of front-end lattice reshaping and deep impurity removal in enhancing the commercial application value of the final zinc iron yellow powder.
[0098] Experimental steps: The final pigment powders of Examples 1 to 4 and Comparative Examples 1 to 5 after being calcined in a rotary kiln and mechanically pulverized were collected as test subjects and placed in a desiccator at room temperature for 24 hours to equilibrate. Weigh an appropriate amount of powder and place it in a special powder press. Press it into a test disc with a flat surface under constant pressure. Use a standard spectrophotometer calibrated with a black and white calibration plate to obtain the CIELAB color space parameters of each sample and record the lightness index L*, redness index a and yellowness index b. According to the standard testing ratio, weigh 1.0 g of zinc iron yellow powder to be tested and 10.0 g of reference titanium dioxide powder, and add a certain amount of refined flaxseed oil; The above mixture is placed on an automatic flat grinder, and a constant load and number of grinding cycles are set to grind and mix thoroughly to produce pigment paste; The color paste was evenly coated onto a standard glass plate using a wet film preparation device. After the coating was completely dry, its reflectance was measured using a reflectometer. The relative coloring power of each group of samples was calculated and compared with the tinting strength of pure zinc iron yellow, which is set as 100% of the industry standard.
[0099] The experimental results are shown in Table 4: Table 4: Macroscopic Pigment Performance Test Data of Final Zinc Iron Yellow Product
[0100] in conclusion: Figure 4This is a comparison chart of the macroscopic pigment performance of the final zinc-iron yellow products from various process schemes of this invention. Sub-figure (a) records the lightness index L* of each test object through solid-line hollow squares, and records the yellowness index b*, which determines the color orientation of the product, through dashed gray-centered dots; Sub-figure (b) uses a structure with a 100% standard baseline to present the relative tinting strength of the products of each scheme with solid triangular broken lines. The thick gray vertical lines below the baseline in the figure intuitively reflect the extent of defects in the optical covering performance of some comparative products.
[0101] According to the data in Table 4, the expression of pigment powder at the macroscopic optical level constitutes a true reflection of the front-end liquid-phase medium control and solid-phase crystallization process. In long-term research on industrial solid waste resource utilization, it can be observed that iron oxides obtained by direct neutralization and precipitation of waste acid often exhibit a dark brown color that lacks commercial application value after undergoing dehydration phase transformation in a rotary kiln.
[0102] The data from Comparative Example 1 clearly reflects this industrial pain point: its brightness is only 52.3, its yellowness has declined to 32.7, while the redness, representing the impurity phase, has abnormally increased to 16.4, and its tinting strength has plummeted to 74.2%. Exploring the root cause of this optical performance degradation, combined with the performance in the earlier washing stage, reveals that the violent and disordered nucleation in the early stages of precipitation resulted in a high concentration of chloride ions encapsulating within the material. These residual chloride ions, located in the interstitial spaces of the crystal lattice, acted as thermodynamic catalysts inducing severe lattice distortion during the high-temperature roasting stage. This caused the originally uniform zinc-iron spinel or goethite phase structure to partially collapse, transforming into a dark hematite impurity phase, severely weakening the selective reflectivity of the powder to visible light.
[0103] Temperature decoupling and the intervention of a composite crystal form regulator completely reversed this situation. In Example 2, the yellowness reached 53.5, the lightness climbed to 68.1, and the relative tinting strength exceeded the industry benchmark for pure products by 125.6%. Under the template constraint of the composite complexing agent, the precursor microcrystals generated in the early stage of the reaction were not randomly aggregated amorphous gels, but precursor microcrystals with highly uniform size.
[0104] The flexible, long-chain polyethylene glycol polymer entanglement disrupts irregular connections on the crystal planes, ensuring the absence of closed capillary channels within the particles. This allows the washing process to easily and thoroughly remove chloride ions that interfere with lattice rearrangement. When this pure and dense precursor enters the rotary kiln, the isomorphic substitution of zinc and iron ions during dehydration is successfully completed with low thermodynamic resistance. The resulting crystal particles have a uniform refractive index distribution and fewer grain boundary defects. Incident light exhibits highly consistent scattering and reflection upon contact with these dense, high-purity crystal surfaces. The correction of pre-processing parameters ultimately realizes the added value of the material at the photonic interaction level of the final product.
Claims
1. A production process for separating and recovering waste acid from hot-dip galvanizing to prepare high-performance zinc-iron yellow, characterized in that, Includes the following steps: The hot-dip galvanized waste acid is pumped into the main reactor, and the mother liquor of the composite complex crystal form regulator is added and stirred and mixed. Then, urea is added and stirred and dissolved to obtain a mixed reaction solution. Start the external circulation system connected to the main reactor, draw the mixed reaction liquid out of the main reactor, and spray it back into the main reactor for circulation after passing through a tubular heat exchanger and a Venturi jet in sequence; Open the air intake port of the Venturi jet injector to draw in air and oxidize the mixed reaction liquid in the circulation. When the pH value and residual ferrous ion concentration of the reaction system reach the preset conditions, stop the air intake and circulation operation to obtain a mixed slurry. The mixed slurry is fed into a filter press for filtration. The filter cake obtained by filtration is washed with deionized water. After the chloride ion concentration in the washing liquid reaches the preset condition, compressed air is introduced to dehydrate the washed filter cake to obtain zinc iron yellow precursor filter cake. The zinc-iron yellow precursor filter cake is fed into a calcination device for calcination, followed by cooling and pulverization to obtain the final zinc-iron yellow pigment powder. The composite complex crystal form regulator mother liquor was prepared by mixing sodium lignosulfonate and polyethylene glycol 400 in water at a mass ratio of 1:(0.1-0.3). The preparation process of the mother liquor of the composite complex crystal form regulator includes: The sodium lignosulfonate was added to deionized water to prepare an aqueous solution with a mass fraction of 15.0% to 20.0%. The polyethylene glycol 400 was added dropwise to the aqueous solution while stirring at a speed of 200-300 rpm. Heat the mixed solution to 60–70°C, stir at a constant temperature for 1.5–2.5 hours, and then cool it to room temperature. After starting the external circulation system connected to the main reactor, the synchronous temperature control of the main reactor and the tubular heat exchanger specifically includes: The main reactor is heated at a heating rate of 0.8–1.5 °C / min to keep the temperature of the material inside the reactor constant at 85–95 °C. The tubular heat exchanger is used to cool the material in the pipeline, so that the temperature of the mixed reaction liquid flowing through the front section of the Venturi jet is maintained at 55-65°C.
2. The production process according to claim 1, characterized in that, The hot-dip galvanizing waste acid specifically includes: The concentration of ferrous ions is 80.0–120.0 g / L; The concentration of divalent zinc ions is 20.0–50.0 g / L; The concentration of free hydrochloric acid is 0.5–2.0 mol / L, and the initial temperature when pumped into the main reactor is controlled at 20–30°C. The amount of the composite complex crystal form regulator mother liquor added, based on the converted pure solid content, accounts for 1.0% to 2.5% of the total mass of the hot-dip galvanizing waste acid.
3. The production process according to claim 1, characterized in that, The specific steps of opening the air intake port of the Venturi jet injector to draw in air include: Air is drawn in using fluid negative pressure, with the intake volume controlled at 0.3–0.8 Nm. 3 / (h·m) 3 ); The pH value and residual ferrous ion concentration of the reaction system meet the preset conditions, including an online pH meter reading within the range of 4.8 to 5.2, and a residual ferrous ion concentration below 0.1 g / L.
4. The production process according to claim 1, characterized in that, The step of feeding the mixed slurry into a filter press for filtration and washing the filter cake obtained by filtration with deionized water specifically includes: The mixed slurry is pumped into a plate and frame filter press, and the pressure of the feed pump is set to 0.4-0.6 MPa; After no continuous filtrate flows out of the outlet, deionized water is used for washing. The pressure of the washing water is controlled at 0.5-0.7 MPa, and the amount of washing water used per unit mass of dry filter cake is controlled at 1.5-2.5 L / kg.
5. The production process according to claim 1, characterized in that, After the chloride ion concentration in the washing solution reaches a preset condition, compressed air is introduced to dehydrate the washed filter cake, resulting in a zinc iron yellow precursor filter cake. Specifically, the filter cake includes: When the chloride ion concentration in the washing solution is below 100 mg / L, stop using deionized water for washing; Compressed air at a pressure of 0.3 MPa to 0.6 MPa is introduced to purge and dehydrate the filter cake for 15 to 25 minutes. The filter cake containing the zinc iron yellow precursor is then unloaded.
6. The production process according to claim 1, characterized in that, The zinc-iron yellow precursor filter cake is fed into a roasting device for roasting, followed by cooling and pulverization, specifically including: The zinc-iron yellow precursor filter cake is transported to a rotary kiln, the heating rate is set to 3-5℃ / min, the temperature is raised to 450-550℃, and constant temperature roasting, oxidation and dehydration is carried out for 2.0-4.0 hours. After roasting, the material is allowed to cool naturally in the furnace to below 80°C before being mechanically crushed.
7. The production process according to claim 1, characterized in that, The process of adding urea and stirring to dissolve it involves calculating the amount of urea to be added based on 1.05 to 1.15 times the theoretically required alkalinity equivalent in the system, and then adding the urea in the form of solid particles into the main reactor for stirring and dissolving.
Citation Information
Patent Citations
Device for preparing ADC (azodicarbonamide) foaming agent by self-suction oxidation
CN103657574A
Method for preparing pigment of zinc ferrite
CN1843940A
